The expansion of criminal law in new technologies - Osorio Redrobán, Vanessa Lizbeth (2023)
The irrational typification of new principles without taking into account the limitations of the Ius puniendi has caused the derivative of the so-called penal expansionism, thus delegitimizing the intervention of punitive power. Therefore, it is essential to analyze the factors that cause the irrational expansion of Criminal Law, among which are: international demands, the feeling of citizen insecurity, as well as punitive populism. Additionally, within the present work, some lines will be allocated to raise the consequences of this phenomenon of criminal expansion such as: the increase in Symbolic Criminal Law, as well as the direct violation of principles; An example of this is the crime of child grooming, included in Spanish criminal law in 2015, of which a dogmatic-criminal analysis will be carried out.